A controllable strategy for the self-assembly of WM nanocrystals/nitrogen-doped porous carbon superstructures (M = O, C, P, S, and Se) for sodium and potassium storage. Issue 4 (8th January 2020) - Jiao, Xiaojuan; Liu, Xiaojie; Wang, Beibei; Wang, Gang; Wang, Xiujuan; Wang, Hui
Abstract : A series of WM (M = O, C, P, S, and Se) nanocrystals/N-doped porous carbon superstructures with superporous structures were generated and the resulting WSe2 /N–PC superstructure was used as anode for both sodium and potassium storage. Abstract : Complex superstructures assembled from simple building blocks have attracted a wide range of interest in engineering materials due to their synergistic and enhanced properties. Herein, a controllable and effective strategy to assemble hierarchical superstructures using a W-polydopamine (W-PDA) complex as the binder and SiO2 @C solid spheres as the blocks is demonstrated. The micro-sized complex 3D W-PDA superstructure assembled from SiO2 @C solid spheres is first formed in a water/ethanol system through the side-by-side assembly mechanism. After carbonization, phosphorization, sulfuration and selenization heat treatment and etching processes, a series of 3D complex superstructures with WM (M = O, C, P, S, and Se) nanocrystals and N-doped porous carbon (N–PC) with superporous structures derived from SiO2 blocks are generated. The well-organized WM nanocrystals can provide more active sites for Na + /K + insertion and extraction, while the N-doped carbon matrix with superporous structures can enhance electrical conductivity and stabilize the structural integrity of the overall electrode. As a proof of concept, the WSe2 /N–PC superstructure with a large interlayer space displays preeminent rate performance and remarkable cycling stability for both SIBs (390 mA h g −1 at 0.1 A g −1 over 200 cycles) and PIBs (220 mA h g −1 at 0.1 A g −1 over 200 cycles). This approach will open an avenue to new multifunctional complex superstructures for more energy storage and conversion applications.